An analysis of student teaching programs in the United States with implications for the government training colleges in Guyana - Singh, Ramlaykha (1973)
This study sought to: (a) review standard and innovative practices in student teaching from selected colleges and universities in the United States, and (b) identify those desirable common characteristics of selected programmes that could be adapted to improve student teaching at the Government Training College in Guyana. Data were collected through letters sent to Directors of Student Teaching at 25 selected institutions in the United States, and personal interviews with 12 selected persons who were directly involved with student teaching programmes in Guyana. Recommendations were classified into two major areas: I) general and specific recommendations that were organized into seven major areas: 1) development of a rationale for the purpose, philosophy, goals, and objectives of the student teaching programme in Guyana; 2) the formulation of guidelines through which the roles and responsibilities of the following could be identified: (a) Ministry of Education, (b) principal of the Government Training College, (c) tutors, (d) headmasters of cooperating public schools, and (e) student teachers; 3) development of a programme with guidelines for: (a) placement of student teachers in the field, and (b) general orientation of student teachers; 4) development of a programme for the selection and training of cooperating teachers; 5) formulation of guidelines for the overall evaluation of student teachers in the field; 6) integration of both segments of the practice teaching assignment into one quarter or semester of continuous supervision by tutors or cooperating teachers; and 7) development of a systematic programme and guidelines for the comprehensive evaluation of the total student teaching programme; and II) recommendations that required further consideration by the Ministry of Education: these were in the areas of: 1) honoraria for cooperating teachers, 2) internships, 3) early field experiences, and 4) inservice training for headmasters and cooperating teachers
Keywords: Government Training College